Breeding of broad-spectrum bacteriocin-producing lactic acid bacteria in traditional fermented dairy products - LIU Caiyun, MA Heping, ZHANG Wenqi, WANG Jie, PENG Zhangpu, SHAO Jianning (Zhongguo niangzao)
To breed broad-spectrum bacteriocin-producing lactic acid bacteria, 96 strains of lactic acid bacteria isolated and purified from tradition fermented dairy products in Gansu province were screened by agar diffusion assay, and the bacteriocin-producing strains were determined. The strains with the optimal antibacterial effect were mutated by heavy ion beam 12C6+ irradiation, and the broad-spectrum antibacterial performance on six indicator bacteria was compared by culture dish partition method. The results showed that the bactericin-producing strain Lp1 with the optimal bacteriostatic effect was selected, and 98 mutant strains were obtained by irradiation mutation. Five mutant strains (L088, L087, L063, L049, L010) with significantly better antibacterial performance against Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Salmonella, Shigella and Cronobacter were screened for broad-spectrum antibacterial performance, and were significantly better than those of the original strain Lp1. Among them, strains L088 and L063 had better broad-spectrum antibacterial performance, the radius of inhibition annular sector of the mutant strain L088 against 6 indicator bacteria increased by 47.81%, 33.28%, 22.97%, 45.25%, 21.39%, and 40.21% than that of the original strain Lp1 respectively, and the radius of inhibition annular sector of the mutant strain L063 against 6 indicator bacteria increased 54.27%, 29.18%, 25.37%, 58.03%, 17.85%, and 42.13%, respectively. The inhibition tests of 6 indicator bacteria could be completed in one Petri dish simultaneously, which could screen the broad-spectrum bacteriocin-producing lactic acid bacteria efficiently.